Secondary transmissions of filariasis caused by nonperiodic form of Brugia malayi among indigenous Dayak people in East Kalimantan - FA.Sudjadi FA Sudjadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Nonperiodic or aperiodic form of Brugia malayi Lichtenstein was discovered and reported recently from East Kalimantan as a new subspecies by Sudjadi, in addition to the nocturnally periodic and subperiodic form, previously known as health problem in many rural areas in Indonesia. The Brugia type was found in high endemicity among Dayak indigenous people who were growing paddy rice by shifting cultivation method in the forest areas in Krayan village, Long Ikis district, Pasir regency.Objectives: To detect secondary transmissions, which so far known unusually happenned on filarial elephantiasis, in the highly endemic of Krayan village, when previous infections have already ceased by entering the chronic stage.Method: Krayan villagers suffering from elephantiasis during previous clinical examinations were recruited in the study. Blood samples (in an amount of 60 mm3) were taken from finger prick to examine the presence of microfilariae.Results: Amount of 17 elephantiasis cases of local inhabitants were examined. Most of them, ie 11 people or 64.7%, were found positif with microfilaremia, with the highest densities of 151 microfilariae per 60 mm3 blood. These unusual cases of secondary transmissions were not only closely related to the high endemicity of filariasis in that Krayan area, but the effective transmissions originated from wild animals in the forest as source of infections as well.Conclusion: The secondary transmissions of filariasis found among indigenous Dayak people in Krayan clearly supports the nonperiodic or aperiodic form of B. malayi filarial worm to be zoonotic or sylvanic.Key words: nonperiodic form of Brugia malayi - elephantiasis - microfilaremia - secondary transmissions -sylvanic filariasis